A ‘civil minority’: Costante Danesi, minority community resilience and Australian democracy, 1918–45 - Dewhirst, Catherine (Queensland review (St. Lucia), 2023)
The figure of Costante Danesi (1884–1969) stands out as an unrelenting defender of the rights of Italian migrants in Queensland’s history between the two world wars. Although his activism as an anti-fascist is documented in archival records and mainstream and Italian-migrant newspapers of the time, his role has received little more than cursory attention by scholars to date. This has led not only to confusion about his politics but also neglect of an opportunity for a deeper appreciation of the intercultural dimensions of resilience during the interwar years. Arriving in Australia in 1921, Danesi was not alone in speaking up to defend Italian migrants’ contributions to society or in aiding their wellbeing, and his activism in protecting their rights aligned with the principles of democracy. Yet an examination of those struggles reveals how the experiences of Italian sugarcane workers in North Queensland exposed overt and covert racism alongside Australia’s democratic ideals of the time. Drawing from the works of Joan Beaumont and Arjun Appadurai, this discussion repositions an Italian-born British subject as significant not only within the history of Queensland but also, more generally, in the demonstration of a minority community’s resilience over this tumultuous era.